The World of Dew and Other Stories - Smith, Julian Mortimer (Book collections on Project MUSE., 2021)
The tales featured in The World of Dew and Other Stories are sometimes terrifying, sometimes touching, sometimes provocative, and occasionally very silly. They function both as windows through which readers can glimpse vast universes waiting to be explored and as mirrors reflecting our own reality back at us in a strange and unfamiliar light.